Clonal integration promotes the growth of Phragmites australis populations in saline wetlands of the Yellow River Delta - Guan, Bo; Yu, Junbao; Wu, Mengdi; Liu, Xiaoling; Wang, Xuehong; Yang, Jisong; Zhou, Di; Zhang, Xiaolong (Frontiers in Plant Science, 2023)
Estuarine wetlands are highly heterogeneous due to strong interactions between freshwater input and seawater intrusion. However, little is known about how clonal plant populations adapt to heterogeneous salinity in soil environments. In the present study, the effects of clonal integration on Phragmites australis populations under salinity heterogeneity were studied using field experiments with 10 treatments in the Yellow River Delta. Clonal integration significantly increased plant height, aboveground biomass, underground biomass, root–shoot ratio, intercellular CO2 concentration, net photosynthetic rate, stomatal conductance, transpiration rate, and stem Na+ content under homogeneous treatment. Under the heterogeneous salt treatment, clonal integration significantly affected total aboveground and underground biomass, photosynthetic traits, and stem Na+ content under different salt gradients. The increase in salt concentration inhibited the physiological activity and growth of P. australis to varying degrees. Compared with the heterogeneous saline environment, clonal integration was more beneficial to P. australis populations in the homogeneous saline habitat. The results of the present study suggest that P. australis prefers homogeneous saline habitats; however, plants can adapt to heterogeneous salinity conditions via clonal integration.